In Power of powers, we learnt the process of how to simplify a term expressed as the power of a power.
For any base number $a$a, and any numbers $m$m and $n$n as powers,
$\left(a^m\right)^n=a^{m\times n}$(am)n=am×n
That is, when simplifying a term with a power that itself has a power:
Here we will look at powers that have variable bases, and also a mix of variable and integer bases. Since "powers of powers" involve expressions with brackets, it's important to remember that everything inside the brackets is raised to the outside power.
Let's say we want to simplify the expression $\left(2x^2\right)^3$(2x2)3:
A common mistake is to only apply the outside power to the algebraic term. If we did this, we would get an answer of $2x^{2\times3}=2x^6$2x2×3=2x6, which is not correct.
Consider the expression in expanded form: $\left(2x^2\right)^3=2x^2\times2x^2\times2x^2$(2x2)3=2x2×2x2×2x2
$\left(2x^2\right)^3$(2x2)3 | $=$= | $2x^2\times2x^2\times2x^2$2x2×2x2×2x2 |
$=$= | $\left(2\times2\times2\right)\times\left(x^2\times x^2\times x^2\right)$(2×2×2)×(x2×x2×x2) | |
$=$= | $2^3\times\left(x^2\right)^3$23×(x2)3 | |
$=$= | $8x^6$8x6 |
You can see that not only is $x^2$x2 multiplied $3$3 times, $\left(x^2\right)^3$(x2)3, but $2$2 is also multiplied $3$3 times, $2^3$23.
So we need to raise $2$2 to the power of $3$3 as well as $x^2$x2 to the power of $3$3.
$\left(2x^2\right)^3=8x^6$(2x2)3=8x6
$\left(-2x^2\right)^3=-8x^6$(−2x2)3=−8x6
Simplify the following, giving your answer with a positive index: $\left(w^3\right)^4$(w3)4
Simplify, and evaluate where possible, the following expression:
$\left(-2x^2\right)^2$(−2x2)2
Simplify the following expression: $\left(3a^3b^2c^3\right)^3$(3a3b2c3)3.